Understanding the Dynamics of Dengue Haemorrhagic Fever (DHF) in Indonesia and its Sustainable Solution: a Qualitative Perspective - Khairulbahri, Muhamad (Science & Technology Asia, 2022)
Dengue haemorrhagic fever (DHF) remains a threat to the global population, especially in tropical regions. In Indonesia, due to population growth and human mobility, almost all Indonesian provinces have experienced DHF. Some efforts have been conducted to eradicate this lethal disease. Owing to these efforts, the fatality rate has decreased significantly. Nevertheless, despite the reduced fatality rate, there is an indication that the incidence rate has increased. Using system archetypes, this paper aims to provide insights into the dynamic patterns of this vector-borne disease, and offers a theoretical premise of why this lethal disease still exists in Indonesia. Upon the application of system archetypes, it was found that a combination of vertical and horizontal mechanisms leads to the persistence of DHF in Indonesia. Fortunately, the Wolbachia strategy offers a promising way to eliminate DHF incidence.